Quality of Chemically Processed Flying Fish (Hyrundicthys oxycephalus) Waste Silage - L. Ambarwati; I. Andriani; T. Taufik; M. Marsudi (Universitas Bengkulu, 2022)
Flying fish are the fish that are widely found in the waters of the Makassar Strait, especially in Majene Regency. During the harvest season, flying fish leave a lot of waste that pollutes the environment. This research aimed to evaluate flying fish waste silage's physical and chemical qualities. The design used was a completely randomized design (CRD) with four treatments and four replications groups. To process the sample, formic acid at concentrations of 0%, 2.5%, 3%, and 3.5% was used. Anova was applied for data analysis, followed by Duncan's test if the treatments differed significantly. Parameters observed were chemical quality, including crude protein and fat content, total bacteria count, and pH, while physical-chemical quality included aroma, color, and texture of flying fish waste silage. The results showed that the addition of formic acid to fly fish silage had a significant effect (P < 0.05) on protein, fat, pH, and total bacteria levels but had no significant effect (P> 0.05) on the aroma, color, and texture of the hay. This research concludes that chemically processing flying fish silage with the addition of 2.5% formic acid can increase the protein content to the optimum level in the P1 treatment resulting in the highest protein content of 48.81% and the fat content of 1.63%, pH 3.5, total bacteria 4 x 104, sour taste, gray color and liquid texture that can be safely used as raw feed.